Onomastics of the "Chanson de Roland" Or: Why Gaston Paris and Joseph Bédier were both right - Beckmann, Gustav A. (De Gruyter, 2023)
This ambitious study of the proper names of the Chanson de Roland proves that it is more tightly and profoundly structured and considerably richer in depicting reality than generally assumed, and that its prehistory can be traced back (almost) to the Frankish defeat. Paris and Bédier were right on the main point close to their hearts: the song has both the thoroughly sophisticated structure (Bédier) and the imposingly long prehistory (Paris).